Using human urinary extracellular vesicles to study physiological and pathophysiological states and regulation of the sodium chloride cotransporter - Wu, Aihua; Wolley, Martin J.; Fenton, Robert A.; Stowasser, Michael (Frontiers in Endocrinology, 2022)
The thiazide-sensitive sodium chloride cotransporter (NCC), expressed in the renal distal convoluted tubule, plays a major role in Na+, Cl- and K+ homeostasis and blood pressure as exemplified by the symptoms of patients with non-functional NCC and Gitelman syndrome. NCC activity is modulated by a variety of hormones, but is also influenced by the extracellular K+ concentration. The putative “renal-K+ switch” mechanism is a relatively cohesive model that links dietary K+ intake to NCC activity, and may offer new targets for blood pressure control. However, a remaining hurdle for full acceptance of this model is the lack of human data to confirm molecular findings from animal models. Extracellular vesicles (EVs) have attracted attention from the scientific community due to their potential roles in intercellular communication, disease pathogenesis, drug delivery and as possible reservoirs of biomarkers. Urinary EVs (uEVs) are an excellent sample source for the study of physiology and pathology of renal, urothelial and prostate tissues, but the diverse origins of uEVs and their dynamic molecular composition present both methodological and data interpretation challenges. This review provides a brief overview of the state-of-the-art, challenges and knowledge gaps in current uEV-based analyses, with a focus on the application of uEVs to study the “renal-K+ switch” and NCC regulation. We also provide recommendations regarding biospecimen handling, processing and reporting requirements to improve experimental reproducibility and interoperability towards the realization of the potential of uEV-derived biomarkers in hypertension and clinical practice.